Ethnobotany across Landscapes in Indonesia: From Urban Markets to Sacred Forests - Santhyami, S (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Ethnobotany stands at the intersection of biodiversity, cultural heritage, and sustainable development. This lecture explores the dynamic relationships between people and plants across diverse Indonesian landscapes, spanning urban traditional markets to remote sacred forests. Drawing from empirical research conducted in Pasar Gede, a culturally significant traditional market in Surakarta, the presentation highlights how urban ethnobotany thrives within complex multicultural environments. Here, edible, medicinal, and ceremony plants serve not only economic and health-related functions but also act as vessels of cultural identity and memory. The lecture further examines ethnobotanical practices in conservation settings, focusing on sacred forests such as Bukit Badindiang in West Sumatra. Managed through customary law, these forests demonstrate how belief systems, cultural values, and ecological stewardship are deeply intertwined. Local governance based on spiritual and ethical frameworks effectively safeguards rare and ecologically vital plant species, contributing significantly to biodiversity preservation and carbon sequestration. Through case studies, this presentation argues that ethnobotany is not merely about cataloguing plant uses but is an active mechanism for sustaining biocultural diversity. It highlights the urgent need to integrate indigenous knowledge into modern conservation strategies, fostering collaborative models that respect local wisdom while addressing global environmental challenges. Ethnobotany, as demonstrated through these Indonesian landscapes, offers a compelling framework for understanding how culture and nature co-evolve, ensuring resilience for both ecosystems and the communities that depend on them.